Study of Enzymatic Hydrolysis Reaction l-Menthyl acetate using Lipase Enzyme from Candida antarctica Recombined Aspergillus oryzae by In Vitro and In Silico - Yasmin Zafirah; Elvina Dhiaul Iftitah (Institut Atsiri Universitas Brawijaya, 2017)
Research about the hydrolysis of l-menthyl acetate catalyzed by lipase enzyme from Candida antarctica recombined Aspergillus oryzae has been observed by in vitro and in silico. The reaction by in vitro method performed with variations time and solvent. The result obtained that lipase enzyme from Candida antarctica recombined Aspergillus oryzae were able to catalyze the hydrolysis reaction of l-menthyl acetate to produce l-menthol. The best result is observed at 16 hours with ethanol solvent, which give % conversion about 13,76%. The research followed by in silico using the docking method, observed that mechanism between amino acid residues to macromolecules as well as the influence of solvents on such interactions. The residues that involved in the reaction are Glu, Thr, Asp, Gln, Ser, His. The ethanol solvent shows a good interaction with macromolecules by forming hydrogen bonds.